Maksimasi Produk Avtur Dengan Pengaturan Cutting Point Di Kolom Fraksinasi Unit Hydrocracking Complex - Zami Furqon; Rediansyah Tito Bisono; Sinung Bayu Nugroho (Jurnal Ilmiah Teknik Kimia, 2021)
Fractionator in the HCC Unit, is a type of atmospheric distillation process that processes types of oil from various sources such as HVGO and HCGO at the HCC Unit to obtain products in the form of LPG, light naphtha, heavy naphtha, Light Kerosene, Heavy Kerosene, diesel and Net Bottom Fractionation. Changes in Cutting Point on Heavy Kerosene products will have an impact on changes in Heavy Kerosene yield and operating conditions on the fractionation column, namely the Heavy Kerosene draw tray. A decrease in the Cutting Point between Heavy Kerosene and Diesel by 5 °F can increase the yield of Heavy Kerosene products to reach 0.78% volume on crude or 1.57 m³/hour. That is, the temperature of the Heavy Kerosene draw tray is 224°C. This is done in order to reduce the cutting point temperature of Heavy Kerosene which can increase the yield of Heavy Kerosene products.